2022
DOI: 10.1021/acs.est.1c07729
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Chemical Transformations of Humic-Like Substances and Further Cognitions Revealed by Optical Methods

Abstract: Humic-like substances (HULIS) are macromolecular complex groups in water-soluble organic compounds (WSOC). pH is a crucial factor that influences the chemical transformations of HULIS in atmospheric particles, but this has been rarely investigated, especially under varying pH conditions. This study attempted to unveil the chemical transformation mechanisms of HULIS under a range of pH conditions using optical methods. The pH-dependent light absorption and fluorescence properties of HULIS were comprehensively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 67 publications
3
9
0
Order By: Relevance
“…6 are consistent with the results of Y. Qin et al (2022), who characterized water-soluble BrC in Beijing and observed a non-linear relationship between AAE and pH, with significant reductions in AAE at pH > 6. This is likely due to chromophores with pKa values above 6.…”
Section: Resultssupporting
confidence: 91%
“…6 are consistent with the results of Y. Qin et al (2022), who characterized water-soluble BrC in Beijing and observed a non-linear relationship between AAE and pH, with significant reductions in AAE at pH > 6. This is likely due to chromophores with pKa values above 6.…”
Section: Resultssupporting
confidence: 91%
“…This type of spectral shift is most likely promoted by changing the acid–base equilibria resulting from the sample dilution. There are known precedents for the absorption spectra of atmospherically relevant compounds to be pH-dependent, for example, the spectra of nitrophenols shift to longer wavelengths at basic pH due to the formation of phenolates. There have been other studies that show that the absorption properties of imidazole-2-carboxaldehyde and pyruvic acid can be altered depending on the pH on its environment, which is prompted by acid base equilibria. , Additionally, the pH dependence of aerosol absorption has also been detected in field samples collected in southeastern United States and Beijing. , It should also be recognized that a large number of acid–base indicators change their spectra at well-defined pH points. It appears that the (currently unidentified) chromophoric products produced from α-pinene SOA in the presence of concentrated sulfuric acid have such similar halochromic properties.…”
Section: Resultsmentioning
confidence: 99%
“… 77 , 78 Additionally, the pH dependence of aerosol absorption has also been detected in field samples collected in southeastern United States and Beijing. 79 , 80 It should also be recognized that a large number of acid–base indicators change their spectra at well-defined pH points. It appears that the (currently unidentified) chromophoric products produced from α-pinene SOA in the presence of concentrated sulfuric acid have such similar halochromic properties.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of pH could be attributed to the protonation or deprotonation of phenolic groups, which affects the electron distribution of the π-conjugated fluorophores, 45 thus influencing the fluorescence intensity and/or position. The pH-dependent fluorescence has been found in aerosol samples collected in China 46,47 and in natural lake water collected in Sweden. 48 At different initial pH values, the measured fluorescence peaks were similar approximately at Ex/ Em = 315/440 nm after an illumination period of 1 h, and the peak intensities were higher under more acidic conditions, all lower than those before illumination.…”
Section: Syrald Photooxidation In Aqueous Solutionsmentioning
confidence: 99%